2015
DOI: 10.14295/aohl.v21i2.673
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrical conductivity on water uptake and vase life of cut gladiolus stems

Abstract: Several experiments reveal that distilled water varies among different laboratories and also does not have a standard composition. Water electrical conductivity (EC) of vase solution is one of the parameters that influence the water uptake by cut flowers. Therefore, the objective of this work was to evaluate the influence of electrical conductivity on water uptake and vase life in cut stems of gladiolus. The stems harvested and kept in distilled water (pH 6.6, EC <0.01dS m -1 ) and tap water (pH 7.0, EC 0.75 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Besides, the stems kept in distilled water had higher water uptake (Ahmad et al, 2013). The presence of ions in the vase solution may increase the overall vase life (da Costa, 2015). The poor performance of tuberose spikes kept in tap water from various sources of tap water could be due to greater variation in physico-chemical properties which greatly affect postharvest longevity and water relations of the cut flowers (Saleem et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the stems kept in distilled water had higher water uptake (Ahmad et al, 2013). The presence of ions in the vase solution may increase the overall vase life (da Costa, 2015). The poor performance of tuberose spikes kept in tap water from various sources of tap water could be due to greater variation in physico-chemical properties which greatly affect postharvest longevity and water relations of the cut flowers (Saleem et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, shorter vase life of tuberose cut spike (Table 3) and florets (Table 4) characteristics in vase solution containing canal water and various sources of tap water might be related to higher pH, EC and soluble salts ( Table 1). Presence of ions in the vase solution may increase the overall vase life and improve water uptake of flowers with favorable optimal EC between 0.60 to 0.87 dS m -1 (da Costa, 2015). The study concluded that tuberose spikes kept in carbonated plus distilled water (1:1) had longer vase life, highest water uptake, more relative fresh weight, delayed florets opening time, more open florets percentage and superior quality as compared to all other water sources followed by in distilled, deionizes and reverse osmosis water.…”
Section: Discussionmentioning
confidence: 99%
“…Cut flowers have limited shelf life due to the depletion of organic reserve compounds by respiration (Finger et al, 2016), bacteria and fungi infection (Muñoz et al, 2019), withering (Elhindi, 2012a), mechanical damage (Fernandes et al, 2020), storage temperature (Menegaes et al, 2019), water quality (Van Doorn, 2012;Costa et al, 2015a), and increase on ethylene sensitivity (Khunmuang et al, 2019). Respiration is inversely related to potential postharvest storage (Tinebra et al, 2021), especially in flowers in which organic respiratory reserves are minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to unsuitable temperatures for long periods also negatively affects the life span of cut flowers (Çelikel and Reid, 2002). Water quality and presence of contaminants, such as fungi or bacteria, or the high content of salts, especially chlorine, also impair their shelf life (Costa et al, 2015a). Despite the influence of ethylene in reducing the life span of ornamental crops, many cut flowers respond to the application of abscisic acid, gibberellins, and cytokinins (Khunmuang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation